Challenges and Strategies to Enhance Quality Learning of Early Childhood Education during the Covid-19 Pandemic: A Qualitative Study in Secang District, Magelang, Central Java, Indonesia - Alfi Nurfita Chasanah; Yuniasih Purwanti (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2022)
The closure of school activities in Indonesia because of the Covid-19 pandemic brought a spontaneous shift from face-to-face learning to online learning. Early childhood education teachers were challenged to thoughtfully deliver a good quality lesson with the resource limitation due to pandemics. This study directly responds to the challenges and strategies of early childhood teachers to enhance quality learning during the Covid-19 Pandemic. This qualitative study surveyed teachers in the Secang district, one of the rural areas in Indonesia. The study shows that equity concern, digital tools and skills, and decreasing the quality of education were challenges that they experienced during Covid-19 pandemics. Home visits and blended learning were strategies that they used to enhance the learning quality of early childhood education. The paper concluded with implications for stakeholders to elaborate on online teaching and learning and strategies for supporting teachers in the Covid-19 pandemic.